Brain insulin and insulin receptors in aging and sporadic Alzheimer's disease - Frölich, Lutz; Blum-Degen, D.; Bernstein, H.-G.; Engelsberger, S.; Humrich, J.; Laufer, S.; Muschner, D.; Thalheimer, A.; Türk, A.; Hoyer, Siegfried; Zöchling, R.; Boissl, K. W.; et al. (Journal of neural transmission, 1998)
The search for the causes of neurodegenerative disorders is a major theme in brain research. Acquired disturbances of several aspects of cellular metabolism appear pathologically important in sporadic Alzheimer's disease (SDAT). Among these brain glucose utilisation is reduced in the early stages of the disease and the regulatory enzymes important for glucose metabolism are reduced. In the brain, insulin, insulin-like growth factors and their receptors regulate glucose metabolism and promote neuronal growth. To detect changes in the functional activity of the brain insulin neuromodulatory system of SDAT patients, we determined the concentrations of insulin and c-peptide as well as insulin receptor binding and IGF-I receptor binding in several regions of postmortem brain cortex during aging and Alzheimer's disease. Additionally, we performed immunohistochemical staining with antibodies against insulin in neocortical brain areas in SDAT and controls. We show for the first time that insulin and c-peptide concentration in the brain are correlated and decrease with aging, as do brain insulin receptor densities. Weak insulin-immunoreactivity could be demonstrated histochemically in pyramidal neurons of controls, whereas in SDAT a stronger insulin-immunoreactivity was found. On a biochemical level, insulin and c-peptide levels were reduced compared to middle-aged controls, but were unchanged compared to age-matched controls. Brain insulin receptor densities in SDAT were decreased compared to middle-aged controls, but increased in comparison to age-matched controls. IGF-I receptor densities were unchanged in aging and in SDAT. Tyrosine kinase activity, a signal transduction mechanism common to both receptor systems, was reduced in SDAT in comparison to middle-aged and age-matched control groups. These data are consistent with a neurotrophic role of insulin in the human brain and a disturbance of insulin signal transduction in SDAT brain and favor the hypothesis that insulin dependent functions may be of pathogenetic relevance in sporadic SDAT.